Two-Way Commuting: Asymmetries from Time Use Surveys - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2021)
Daily commuting of workers is a complex phenomenon that has attracted research attention for many years and, despite the significant literature acknowledging differences between morning and evening commuting, commuting to and from work are considered symmetric trips in much of the prior research. We explore the asymmetries in time spent commuting to and from work, in seven countries, using detailed time use records from the Multinational Time Use Study (MTUS). We focus on the duration, mode of transport, and timing of commuting trips, and we provide evidence on what socio-demographic characteristics are related to such asymmetries. We find that commutes to work (usually in the morning) last longer than commutes from work (usually in the afternoon or evening), although there are quantitative differences among countries. The timing of commuting also differs across countries, although commutes to work are more concentrated at certain hours in the morning than commutes from work. Our results may serve for a better design of public policies that take this heterogeneity into account in the commuting behavior of different population groups.
Keywords: R40; O57; 330; two-way commuting; commuting symmetries; time use survey; Multinational Time Use Study